Effect Of Market Waste Bokashi Dosage On Growth And Production Of Sweet Corn (Zea Mays L.saccharata) In Polybag - Sunarti Sunarti; Sri Mulatsih; Rio Rizki Putra (University of Prof. Dr. Hazairin, SH, 2022)
This research aims to: determine the effect of market waste bokashi dose on growth and yield of sweet corn; to determine the dose that can give the best effect on the growth and yield of sweet corn. The research was carried out from January 2021 to March 2021. The research was carried out on dry land located in Kembang Seri Village, Talang Empat sub-district, Central Bengkulu. The study used a non-factor randomized block design (RAK) consisting of six (6) treatments and three (3) replications, so that there were eighteen (18) experimental units. Consisting of seven (7) plants so that in total there were 126 experimental units (126 polybags). The results showed that the dose of Bokashi Market Waste gave the best results on the Growth and Yield of Sweet Corn (Zea mays) in polybags at a dose level of 15 tons/ha. At a dose of 15 tons/ha the plant showed the best effect on plant height, stem diameter, wet root weight, dry plant weight, length of ear and weight of cob